1996
DOI: 10.1597/1545-1569(1996)033<0067:nsfonm>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Novel Stimuli for Obtaining Nasalance Measures from Young Children

Abstract: The use of novel stimuli for obtaining nasalance measures in young children was the focus of this study. The subjects were 20 children without a history of communication disorders and 20 children at risk for velopharyngeal insufficiency (VPI). Each subject recited three passages; the standard Zoo Passage, and two novel stimuli that were named the Turtle Passage and the Mouse Passage. Like the Zoo Passage, the Turtle Passage contained no normally nasal consonants. The Mouse Passage was about 11% nasal consonant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 0 publications
0
22
0
1
Order By: Relevance
“…One study with graduate students with experience in rating resonance disorders found good correlation between perceptual ratings and nasalance scores (Watterson et al 1996), the other study showed only moderate correlation (Watterson et al 1993). In both studies a practice session was included before the rating of the actual study's voices.…”
Section: Discussionmentioning
confidence: 99%
“…One study with graduate students with experience in rating resonance disorders found good correlation between perceptual ratings and nasalance scores (Watterson et al 1996), the other study showed only moderate correlation (Watterson et al 1993). In both studies a practice session was included before the rating of the actual study's voices.…”
Section: Discussionmentioning
confidence: 99%
“…Nasalance is an acoustic measure that has gained widespread acceptance as a diagnostic correlate of perceived oral-nasal resonance balance (e.g., Dalston et al, 1991;Hardin et al, 1992;Watterson et al, 1996). The term nasalance was coined by Fletcher (1978) to represent the output of a dual-microphone device called TONAR II.…”
Section: Abstract: Nasalance Transpalatal Nasalance Velopharyngealmentioning
confidence: 99%
“…The technique estimates the velopharyngeal function indirectly, by measuring nasalance, a physical magnitude that corresponds to the relative amount of nasal acoustic energy during production of oral sounds (14) , according to the spoken language. Nasalance scores must be obtained from standardized speech samples, which are composed of exclusively oral or predominantly nasal consonants, in order to diagnose hypernasality or hyponasality, respectively (15,16,17) . Speech stimuli may be of high pressurecontaining plosive, fricative, and affricate consonants, or of low pressure -containing vowels and liquid consonants (18) .…”
Section: Introductionmentioning
confidence: 99%